Plant rDNA database: update and new features - Garcia, Sònia; Gálvez, Francisco; Gras, Airy; Kovařík, Aleš; Garnatje, Teresa (Database, 2014)
UNLABELLED: The Plant rDNA database (www.plantrdnadatabase.com) is an open access online resource providing detailed information on numbers, structures and positions of 5S and 18S-5.8S-26S (35S) ribosomal DNA loci. The data have been obtained from >600 publications on plant molecular cytogenetics, mostly based on fluorescent in situ hybridization (FISH). This edition of the database contains information on 1609 species derived from 2839 records, which means an expansion of 55.76 and 94.45%, respectively. It holds the data for angiosperms, gymnosperms, bryophytes and pteridophytes available as of June 2013. Information from publications reporting data for a single rDNA (either 5S or 35S alone) and annotation regarding transcriptional activity of 35S loci now appears in the database. Preliminary analyses suggest greater variability in the number of rDNA loci in gymnosperms than in angiosperms. New applications provide ideograms of the species showing the positions of rDNA loci as well as a visual representation of their genome sizes. We have also introduced other features to boost the usability of the Web interface, such as an application for convenient data export and a new section with rDNA-FISH-related information (mostly detailing protocols and reagents). In addition, we upgraded and/or proofread tabs and links and modified the website for a more dynamic appearance. This manuscript provides a synopsis of these changes and developments. DATABASE URL: http://www.plantrdnadatabase.com.
Keywords: Plants; DNA rostlinná; Databases, Genetic; ribozomální DNA; Database Management Systems; systémy řízení databází; Computational Biology; DNA, Plant; internet; Internet; DNA, Ribosomal; databáze genetické; rostliny; výpočetní biologie